2011
DOI: 10.1002/jpln.200900210
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in total microbial activity and nitrification rates in soil due to amoxicillin‐spiked pig manure

Abstract: Most veterinary drugs enter the environment via manure application. However, ecotoxic effects of antibiotics are varying as a function of their physicochemical characteristics and for most antibiotics it is still unclear how these substances interact with soil biota. It was the aim of the present study to investigate effects of manure containing different concentrations of the antibiotic amoxicillin (AMX) on microbial‐community function in two different soils over an incubation time of 18 d. Therefore, soil re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
0
15
1
2
Order By: Relevance
“…The non-nitrogen-related studies involved sulfatereduction (Hansen et al 1992;Ingvorsen et al 2003;Liu et al 2014), pyrene degradation (Näslund et al 2008), iron reduction (Thiele-Bruhn and Beck 2005; Toth et al 2011), arsenic oxidation and reduction (Yamamura et al 2014), methanogenesis (Conkle and White 2012;Fountoulakis et al 2004;Liu et al 2014), and acetate biodegradation kinetics (Wunder et al 2013). We only found a few studies that examined the effect of antibiotics on several biogeochemical processes (Conkle and White 2012;Kotzerke et al 2008;Kotzerke et al 2011;Liu et al 2014;Rosendahl et al 2012;Toth et al 2011). …”
Section: Effects On Biogeochemical Processesmentioning
confidence: 94%
See 2 more Smart Citations
“…The non-nitrogen-related studies involved sulfatereduction (Hansen et al 1992;Ingvorsen et al 2003;Liu et al 2014), pyrene degradation (Näslund et al 2008), iron reduction (Thiele-Bruhn and Beck 2005; Toth et al 2011), arsenic oxidation and reduction (Yamamura et al 2014), methanogenesis (Conkle and White 2012;Fountoulakis et al 2004;Liu et al 2014), and acetate biodegradation kinetics (Wunder et al 2013). We only found a few studies that examined the effect of antibiotics on several biogeochemical processes (Conkle and White 2012;Kotzerke et al 2008;Kotzerke et al 2011;Liu et al 2014;Rosendahl et al 2012;Toth et al 2011). …”
Section: Effects On Biogeochemical Processesmentioning
confidence: 94%
“…Across studies, the fate of the antibiotic substance during the experiment was often unconsidered, and only 40 % of the studies quantified the antibiotic concentration in the experimental medium to determine the effect on a certain process (Ahmad et al 2014;Campos et al 2001;Hansen et al 1992;Hou et al 2015;Kotzerke et al 2008;Kotzerke et al 2011;Liu et al 2014;Rico et al 2014 Effective concentration Effective concentration Rosendahl et al 2012;Thiele-Bruhn and Beck 2005;Yan et al 2013). Regardless the antibiotic family, these studies revealed considerable loss of antibiotics over the experiment.…”
Section: Effects On Biogeochemical Processesmentioning
confidence: 96%
See 1 more Smart Citation
“…The decrease in AOB and AOA abundance could be due to the inoculation of P. lilacinus, which occupied some of rhizosphere space and increased the depletion of ammonium and other nutrients (Qiu et al 2014). Bioactive compounds can inhibit soil microbial activity and N-transformations Kotzerke et al 2011). Fungi belonging to the genus Paecilomyces can synthesize a wide range of bioactive compounds, including pyridone alkaloid inhibiting acetylcholinesterase activity (Teles and Takahashi 2013) and cyclohexadepsipeptide showed cytotoxicity to two cancer cell lines (Isaka et al 2007).…”
Section: Effects Of P Lilacinus On the Abundance Of Aob And Aoamentioning
confidence: 98%
“…As novel persistent pollutants, antibiotics were included in limitations issued by the Food and Agriculture Organization (FAO) and the USA. High concentrations of antibiotics in the sludge would have negative impacts on the environment if the sludge were applied on agricultural land, including effects on soil microbial diversity, respiration and denitrification due their antimicrobial activities Kotzerke et al, 2011;Zielezny et al, 2006).…”
Section: Impacts On Soil Microorganisms and Soil Enzyme Activitymentioning
confidence: 99%